Spiritual counseling on anxiety level in (Lombok) Indonesian earthquake victims - Zurriyatun Thoyibah; Dewi Nur Sukma Purqoti; Elisa Oktaviana (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: An earthquake has an impact on mental health problems. Lombok earthquake victims undergo an anxiety, neurotic, psychotic symptoms, and Post Traumatic Syndrome Disease. Anxiety have an impact on the mind, body and it cause of physical illness. One of the nursing interventions that can be given to deal with anxiety includes spiritual counseling, which is given so that disaster victims accept their conditions, it is not making disaster a burden and reducing anxiety.Purpose: To determine the effect of Spiritual counseling on anxiety level in (Lombok) Indonesian earthquake victims.Methods: Quantitative study with a pre-experimental approach using one group pre-post-test design on 25 earthquake victims in Lombok. The instrument was used the Hamilton Anxiety Rating Scale questionnaire and the standard operational procedures for spiritual counseling. Data were analyzed using univariate analysis and t dependent test.Results: The anxiety score before spiritual counseling was 19.60 ± 3.26, while the anxiety score after spiritual counseling was 10.04 ± 4.13. Statistical tests showed a significant difference between anxiety levels before and after spiritual counseling for earthquake victims in Lombok (p <0.05).Conclusion: Earthquake victims in order to improve their spiritual quality by joining religious activities routinely to calm the mind and reduce anxiety or trauma, it is caused by earthquakes.